An initial broad-level mapping of personality-situation contingencies in self-report data. (1st January 2019) - Conley, Marie N.; Saucier, Gerard
Abstract: It is commonplace observation that situations can affect the expression of personality dispositions. But psychology has typically addressed this relationship in a broad, unspecific way, with little attention yet to which situations might particularly affect which dispositions. Here, our premise is that critical information might arise from examining how a range of specific situations are perceived to affect each of a range of specific personality tendencies. 500 participants completed a questionnaire in which 15 items referencing attributes were juxtaposed with each of 29 differing situations that are salient to laypersons, and patterns compared with scores on a short Big Five (plus Honesty) measure. This design enabled a preliminary mapping of basic personality-by-situation dynamics. Honesty yielded the least variance between situations, with Extraversion and Emotional Stability showing the most. Variation in each personality dimension had its own pattern of situational contingency: for example global Extraversion scores were particularly predicted by extraverted tendencies in situations involving unfamiliar others. The emergence of these patterns suggests that at least some such dimensions are relevant to and diagnosed by responses to a particular limited range of situations.